Application of Gravity Force on Banana Cutting Machines - Nur Hayati; Raka Mahendra Sulistiyo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Indonesian people love to consume bananas as fruit. Many sources of nutrients, including minerals and carbohydrates, are contained in this fruit. Various UMKM (Usaha Mikro, Kecil dan Menengah) have grown by developing processed banana foods such as sale and banana chips. An important step in making processed banana dishes is cutting the bananas. In general UMKM still process bananas using conventional techniques, namely cutting using manual human power. The purpose of this study is to utilize gravity to design a banana cutting machine. Gravity will cause the banana pieces to fall into the storage container. The dimensions of the cutting machine are designed with a small size to facilitate mobility. The results showed that the use of a cutting machine increased the efficiency of banana cutting. A more uniform cutting thickness was achieved.